Potential Of Renewable Wave And Offshore Wind Energy Sources In Malaysia. - Chiang, E.P.; Zainal, Z. A.; Aswatha Narayana, P.A.; Seetharamu, K. N. (2003)
Malaysia is a country vastly surrounded by water. Wave power and offshore wind power has been recognised by the international community as a renewable clean energy source. Analysis was conducted for the potential of wave energy and wind energy along the coastline of Malaysia from the data obtained by the Malaysia Meteorological Service (MMS) from 1985 to 2000.